Brazilian version of the CHOP INTEND scale: cross-cultural adaptation and validation - Renalli Manuella Rodrigues Alves; Alessandra Paula de Melo Calado; Vanessa Van Der Linden; Maria Aparecida Ferreira Chaves Bello; Lívia Barboza de Andrade (Arquivos de Neuro-Psiquiatria)
Background Spinal muscular atrophy (SMA) is a rare genetic disease that causes progressive muscle weakness and impacts motor function. The type I is the most severe presentation and affects infants before 6 months old. In addition, the instruments available for assessing motor function have limitations when applied to infants with neuromuscular diseases and significant muscle weakness.